2003
DOI: 10.1097/01.ju.0000052720.62999.a9
|View full text |Cite
|
Sign up to set email alerts
|

Conformal High Dose Rate Brachytherapy Improves Biochemical Control And Cause Specific Survival in Patients With Prostate Cancer And Poor Prognostic Factors

Abstract: For patients with poor prognostic factors external beam radiation therapy with conformal high dose rate brachytherapy boost improved biochemical control, resulting in a high cause specific survival rate with low toxicity. Another important advantage is that the patient is not radioactive after the high dose rate implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 19 publications
8
46
2
1
Order By: Relevance
“…Arcangeli et al (16) published a report comparing 80 Gy (2 Gy/fraction) versus 62 Gy (3.1 Gy/fraction) and showed that the hypofractionated schedule is superior to the conventional fractionation in terms of freedom from biochemical failure rate with equivalent toxicity. This is also confirmed by studies of high dose rate brachytherapy (HDR BT) (17)(18)(19). Our outcomes are consistent with those that have resulted from HDR BT.…”
Section: Discussionsupporting
confidence: 80%
“…Arcangeli et al (16) published a report comparing 80 Gy (2 Gy/fraction) versus 62 Gy (3.1 Gy/fraction) and showed that the hypofractionated schedule is superior to the conventional fractionation in terms of freedom from biochemical failure rate with equivalent toxicity. This is also confirmed by studies of high dose rate brachytherapy (HDR BT) (17)(18)(19). Our outcomes are consistent with those that have resulted from HDR BT.…”
Section: Discussionsupporting
confidence: 80%
“…[17][18][19][20] In brief, all patients received treatment with external beam radiation using megavoltage linear accelerators (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In all three institutions, the prostate gland was boosted using two interstitial brachytherapy procedures.…”
Section: Radiation Techniquementioning
confidence: 99%
“…Advancements recently made in imaging technology have improved the accuracy and effectiveness of HDR prostate brachytherapy planning. The anatomical information obtained from computed [2,4,17,18,25,26]. In addition, the development of anatomy-based inverse planning dose optimization for HDR brachytherapy can produce a highly conformal dose profile within one minute, with more than 90% of the prostate volume covered with the prescribed dose and a clinically acceptable sparing of OAR [1,3,5,[13][14][15]28].…”
mentioning
confidence: 99%
“…The functional imaging information, MR spectroscopic imaging (MRSI) combined with MRI and translated into the planning CT or MRI, was introduced into HDR prostate brachytherapy in order to better identify dominant intra-prostatic malignant lesions (DILs) within the prostate and to escalate the dose on the DIL [22]. Several clinical follow-up studies demonstrated that improved biochemical control, a higher survival rate and a lower risk of complications are achieved by the dose escalation of prostate cancer with HDR brachytherapy [2,4,17,18,25,26]. In addition, the development of anatomy-based inverse planning dose optimization for HDR brachytherapy can produce a highly conformal dose profile within one minute, with more than 90% of the prostate volume covered with the prescribed dose and a clinically acceptable sparing of OAR [1,3,5,[13][14][15]28].…”
mentioning
confidence: 99%